Lionel W. McKenzie and the Proof of the Existence of a Competitive Equilibrium - E. Roy Weintraub (Duke University, Center for the History of Political Economy (CHOPE), 2011)
The theorem proving the existence of general equilibrium in a competitive economy, which necessarily involved specifying the conditions under which such an equilibrium would exist, is an extraordinary achievement of twentieth-century economics. The discovery is commonly attributed to the paper by Kenneth Arrow and Gerard Debreu, "Existence of an Equilibrium for a Competitive Economy," which was published in the July 1954 issue of Econometrica. However it is less well-known, even within the economics profession, that Lionel McKenzie published a paper in the previous issue of Econometrica, "On Equilibrium in Graham's Model of World Trade and Other Competitive Systems," which discussed many of the same themes. Over the past decade the new availability of archival material, the papers of Lionel McKenzie, Robert Solow, Gerard Debreu, and Leonid Hurwicz, permits a reexamination of the events surrounding the publication of both Econometrica papers in 1954. The discussion raises general issues concerning "simultaneous discovery," "priority," and "credit" in economic research, and opens a window into some academic practices of that time.
Keywords: B2; B3; 330; Arrow-Debreu; McKenzie; General Equilibrium; Arrow-Debreu Model